Footprints of Sepsis Framed Within Community Acquired Pneumonia in the Blood Transcriptome - Hopp, Lydia; Loeffler-Wirth, Henry; Nersisyan, Lilit; Arakelyan, Arsen; Binder, Hans (Frontiers in Immunology, 2018)
We analyzed the blood transcriptome of sepsis framed within Community Acquired Pneumonia (CAP) and characterized its molecular and cellular heterogeneity in terms of functional modules of co-regulated genes with impact for the underlying patho-physiological mechanisms. Our results showed, that CAP severity is associated with immune suppression owing to T-cell exhaustion and HLA and chemokine receptor deactivation, endotoxin tolerance, macrophage polarization and metabolic conversion from oxidative phosphorylation to glycolysis. We also found footprints of host’s response to viruses and bacteria, altered levels of mRNA from erythrocytes and platelets indicating coagulopathy that parallel severity of sepsis and survival. Finally, our data demonstrated chromatin re-modelling associated with extensive transcriptional deregulation of chromatin modifying enzymes, which suggests the extensive changes of DNA methylation with potential impact for marker selection and functional characterization. Based on the molecular footprints identified we propose a novel stratification of CAP cases into six groups differing in the transcriptomic scores of CAP severity, interferon response and erythrocyte mRNA expression with impact for prognosis. Our analysis increases the resolution of transcriptomic footprints of CAP and reveals opportunities for selecting sets of transcriptomic markers with impact for translation of omics research in terms of patient stratification schemes and sets of signature genes.